PHARMACIST COMPETENCY IMPROVEMENT IN STERILE DISPENSING AT HEALTH FACILITY SERVICES IN LAMPUNG - Prof. Dr. Retno Sari, M.Sc., Apt.; Dewi Isadiartuti; Muhammad Agus Syamsur Rijal; Dini Retnowati; Dinda Monika Nusantara Ratri; Nuzul Wahyuning Diyah; Tutik Sri Wahyuni (Jurnal Layanan Masyarakat, 2023)
Sterile dosage forms are pharmaceutical preparations that require to be free of microorganisms and particles. In health services, sterile preparations often undergo a series of changes in form from their original conditions to new products through dissolution or mixing with other sterile preparations. To maintain sterility, sterile preparation dispensing skills are needed. Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016 and No. 74 of 2016 concerning Pharmaceutical Service Standards in Hospitals and Health Centers are intended to improve the quality of pharmaceutical services, guarantee legal certainty for pharmacists and protect patients and the public from irrational drug use in the context of patient safety. Pharmaceutical service standards in hospitals cover the management of pharmaceutical preparations, medical devices, consumable medical materials and clinical pharmacy services. One of the standards in clinical pharmacy services is aseptic/sterile dispensing sterile. The community service aims to increase the knowledge and skills of pharmacists at Bandar Lampung health facilities and its surroundings in managing sterile preparations.The community service is held through a webinar with a zoom platform followed by discussion and aseptic dispensing demonstration. The sterile dispensing demonstration are carried out by dividing the participants into four groups in the breakout room and each group was guided by a facilitator. In this activity, participants were provided with material on formulation, compatibility, and stability of pharmaceutical preparations, dispensing sterile preparations, aseptic techniques, and problems in sterile dispensing sterile at the hospital. The activity was attended by 63 pharmacists from 25 hospitals in Bandar Lampung and its surroundings, also academics in Tanjung Karang. The evaluation results showed an increase in participants' knowledge of 19,3% and participants expected that activities could be carried out periodically with various topics. The activities are expected to improve the patient's health status and enhance the role of the Faculty of Pharmacy, Airlangga University in the National Health System.